THE IMPORTANCE OF TRIZ TECHNOLOGY IN DEVELOPING THINKING SKILLS - Zokirova Sohiba Muxtoraliyevna; Fayzullayeva Nazokat Uchqun qizi (Web of Journals Publishing, 2025)
Formation of skills such as inventiveness and modeling in elementary school students is becoming a modern demand. TRIZ technology is the technology that is suitable for the development of these two abilities. This article talks about the methods and methods of using TRIZ technology in elementary school students.
Keywords: Class, lesson, system, technology, TRIZ, student, teacher, inventiveness, creativity, thought, innovation.